Analyzing Content Promotion Strategies on a Marketplace: A Social Network Study: Studi Analisis Jaringan Sosial Strategi Promosi Konten di Platform Marketplace - Hafif Wisnu Wahyudi; Rita Ambarwati Sukmono (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to examine the user response to content promotion strategies on Bukalapak Marketplace, focusing on interactions related to discounts, free shipping, and cashback. Qualitative research methods were employed, using data collected from Twitter through data pulling and processed using Wordij and Gephi for data filtering. Social Network Analysis (SNA) with Crawl Data was applied to determine the map of interactions on the platform. The results revealed that user response varied across different promotional strategies and time periods. Specifically, the most frequent user response was observed for content promoting